2021
DOI: 10.1021/acs.orglett.1c01892
|View full text |Cite
|
Sign up to set email alerts
|

Borenium-Catalyzed Reduction of Pyridines through the Combined Action of Hydrogen and Hydrosilane

Abstract: Mesoionic carbene-stabilized borenium ions efficiently reduce substituted pyridines to piperidines in the presence of a hydrosilane and a hydrogen atmosphere. Control experiments and deuterium labeling studies demonstrate reversible hydrosilylation of the pyridine, enabling full reduction of the N-heterocycle under milder conditions. The silane is a critical reaction component to prevent adduct formation between the piperidine product and the borenium catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the past decade, notable achievements for the hydrogenation of (hetero)arenes were realised, especially in the case of nitrogen heterocycles, which have an additional defined coordination site as well as lower stabilisation energy. In this respect, the groups of Glorius, 11,12 Du, 13,14 Chirik, 15 Stoltz 16 or more recently Crudden 17 developed protocols utilising either specific homogeneous catalysts, frustrated Lewis pairs or took advantage of auxiliary based approaches. An interesting system for the cis -hydrogenation of non-functionalised arenes was reported by Delferro and Marks, who used a supported organozirconium catalyst with remarkable selectivity.…”
mentioning
confidence: 99%
“…In the past decade, notable achievements for the hydrogenation of (hetero)arenes were realised, especially in the case of nitrogen heterocycles, which have an additional defined coordination site as well as lower stabilisation energy. In this respect, the groups of Glorius, 11,12 Du, 13,14 Chirik, 15 Stoltz 16 or more recently Crudden 17 developed protocols utilising either specific homogeneous catalysts, frustrated Lewis pairs or took advantage of auxiliary based approaches. An interesting system for the cis -hydrogenation of non-functionalised arenes was reported by Delferro and Marks, who used a supported organozirconium catalyst with remarkable selectivity.…”
mentioning
confidence: 99%
“…An alternative strategy for the hydrogenation of pyridines, which also makes use of an electron-deficient boron catalyst, was developed in 2021 by Crudden and co-workers (Scheme ). The authors demonstrated that mesoionic carbene-stabilized borenium ions, in the presence of hydrogen atmosphere and hydrosilanes, promoted a tandem hydrogenation reaction of di- and monosubstituted pyridines under mild conditions . The carbene-stabilized borenium catalyst was generated in situ by hydride abstraction with Ph 3 C + B­(C 6 F 5 ) 4 – from the corresponding precatalyst.…”
Section: Hydroboration Hydrosilylation and Reduction Reactionsmentioning
confidence: 99%
“…The authors demonstrated that mesoionic carbenestabilized borenium ions, in the presence of hydrogen atmosphere and hydrosilanes, promoted a tandem hydrogenation reaction of di-and monosubstituted pyridines under mild conditions. 68 The carbene-stabilized borenium catalyst was generated in situ by hydride abstraction with Ph 3 C + B-(C 6 F 5 ) 4…”
Section: Metal-free Hydroborations Hydrosilylations Andmentioning
confidence: 99%
“…Reasoning that this reduced reactivity is likely due to product-promoted catalyst decomposition, they applied a combined hydrosilylation and hydrogenation approach to suppress such side reactions. 41 Owing to the stronger reducing character of the Si–H bond compared to the B–H bond, this transformation leads to the formation of N -silylated piperidines which are too bulky to form adducts with the borenium catalyst. In the presence of 1.5 equiv.…”
Section: Borenium Catalysed Hydrogenationmentioning
confidence: 99%